Brain mapping indications and techniques - Quiñones-Hinojosa, Alfredo; Chaichana, Kaisorn (Kaisorn L.); Mahato, Deependra (Thieme, 2020)
"Despite advances in imaging techniques to identify eloquent cortical brain regions and subcortical white matter, brain mapping is the only method for obtaining real-time information with high sensitivity and specificity. This groundbreaking technology greatly enhances the neurosurgeon's ability to safely resect challenging lesions located in eloquent areas of the brain. The book starts with discussion of preoperative aspects, including the history of brain mapping and anatomy of eloquent cortical and eloquent white matter tracts. Subsequent chapters cover perioperative aspects of brain mapping including indirect and direct functional mapping, the role of neurophysiology, awake craniotomy operating room set-up and surgical instruments, and anesthetic considerations. Diverse awake and asleep brain mapping techniques are described for various intracranial pathologies, as well as advances in postoperative recovery of neurological function including physical and speech therapy"--